Current status of image-enhanced endoscopy in inflammatory bowel disease - Young Joo Yang (Korean Society of Gastrointestinal Endoscopy, 2023)
In inflammatory bowel disease (IBD), chronic inflammation leads to unfavorable clinical outcomes and increases the risk of developing colorectal neoplasm (CRN); thereby highlighting the importance of endoscopically evaluating disease activity as well as detecting and characterizing CRN in patients with IBD. With recent advances in image-enhanced endoscopic (IEE) technologies, especially virtual chromoendoscopy (VCE) platforms, this review discusses state-of-the-art IEE techniques and their applicability in assessing disease activity and surveillance colonoscopy in patients with IBD. Among various IEE, VCE demonstrated the capacity to identify quiescent disease activity. And endoscopic remission defined by the new scoring system using VCE platform better predicted clinical outcomes, which may benefit the tailoring of therapeutic strategies in patients with IBD. High-definition dye-chromoendoscopy (HD-DCE) is numerically superior to high-definition white light endoscopy (HD-WLE) in detecting CRN in IBD; however, discrepancy is observed in the statistical significance. VCE showed comparable performance in detecting dysplasia to HD-WLE or DCE and potential for optical diagnosis to differentiate neoplastic from nonneoplastic lesions during surveillance colonoscopy. Applying these novel advanced IEE technologies would provide opportunities for personalized medicine in IBD and optimal treatment of CRN in patients with IBD.